A competência da justiça federal para processar e julgar indígenas e os reflexos jurídicos pós-constituição de 1988 - Silva, Marcos Pereira da (2013)
The present study aims at bringing debate to the question of jurisdiction to adjudicate Indian, when the same set up as an author or victim of crime. The 1988 Constitution, in tribute to cultural diversity, has given a new treatment to the Indian, through which must be respected their culture and tradition. Thus, the new constitutional order should produce echo effects throughout constitutional legislation, especially regarding the jurisdiction of federal courts to adjudicate the natives and should therefore be reviewed jurisprudence majority of the Superior Courts, as well as the Supreme Court, with the point initial cancellation of Precedent 140 of the STJ. In criminal law, indigenous people, due to its adequacy should be seen when examining the guilt, so different from the ordinary citizen. It must be respected cultural diversity, assured the Federal Constitution. This time, this research will seek, through research conducted in the jurisprudence of the Supreme Court, Supreme Court and decisions of courts and judges, demonstrate that the Charter, to create a multiethnic state in which it is given a different treatment to minorities, particularly the natives, there arises the need for the cancellation of 140 of the Supreme Court docket, as well as the importance of conducting anthropological report, as a condition for imposition of penalty on criminal offenses committed by Indians. It is hoped, therefore, appeal to the judiciary to the new constitutional order, considering that in progress in the House of Representatives the Statute of Indigenous Society (PL No. 2057-93) and the draft bill of the Senate No. 156 / 09, which provides expressly for compulsory anthropological examination, through the analysis of culpability to be held in error ban.